Sharia Values and Work Motivation: Their Effect on Online Ride-Hailing Drivers’ Performance in Subang: Sharia Values and Work Motivation: Their Effect on Online Ride-Hailing Drivers’ Performance in Subang - Tigin Lugiani; Alie Haq Nur Shofari (STIESA Press, 2026)
ABSTRAK/ABSTRACT This study aims to analyze the influence of work motivation, viewed through both human resource management theory and Islamic work ethics (sharia values), on the performance of online ride-hailing drivers. This research uses a quantitative approach with a simple linear regression analysis method. Data were collected from 30 active online drivers in Subang through questionnaires distributed via Google Forms. The theoretical framework is built upon Maslow's Hierarchy of Needs and the concept of Islamic work motivation as the middle theory, and Human Resource Management as the grand theory. The results of the descriptive analysis indicate that both motivation and performance of the drivers are in the high category. Statistical testing through simple linear regression shows that work motivation has a positive and significant effect on driver performance. These findings imply that high motivation, driven by economic needs, incentives, rating systems, and the intention to earn a lawful (halal) livelihood, encourages drivers to provide better service quality and achieve higher work quantity.